2013
DOI: 10.1111/jace.12160
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Net‐Shaped Porous Ceramics for Potential Sound Absorption Applications at High Temperatures

Abstract: We present an interesting processing route for obtaining alumina/mullite‐based ceramics with controlled porosity and airflow resistance leading to promising microstructures for application as sound absorbers. The use of ceramic materials aims for potential applications where high temperatures or corrosive atmospheres are predominant, e.g., in combustion chambers of gas turbines. For the production of the porous ceramics we combined freeze gelation and sacrificial templating processes to produce near‐net‐shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Previous studies found that sound-absorption performance was determined by the apparent porosity. 8,31,32 An open cellular structure in porous medium caused irregular transmission routes for sound wave. 32 The diffuse reflection or refraction produced by the acoustic wave entering materials increased with increased apparent porosity, impelling the increment of the vibration of the hole wall and consuming sound energy.…”
Section: Fac Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that sound-absorption performance was determined by the apparent porosity. 8,31,32 An open cellular structure in porous medium caused irregular transmission routes for sound wave. 32 The diffuse reflection or refraction produced by the acoustic wave entering materials increased with increased apparent porosity, impelling the increment of the vibration of the hole wall and consuming sound energy.…”
Section: Fac Effectmentioning
confidence: 99%
“…From Figures 5 and 6, small difference of pore-size distribution between FAC was 0 and 1 wt%, but the latter one has high pore connectivity and better acoustic properties. 31,32 The increased numbers of various sizes and morphology open cells with the increment of FAC were beneficial to the absorption of sound waves under different frequencies, resulting in better sound-absorption performance and wider sound-absorption frequency band. The samples with FAC of 4 wt% had a smaller pore-size distribution compared with FAC of 5 wt% ( Figure 6).…”
Section: Fac Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the last calculation step where Eq. (6). is used again with the thermal conductivity obtained by second step calculation as input.…”
Section: Prediction With Analytical Relationsmentioning
confidence: 99%
“…As examples, porous ceramic structures are used as filters for molten metal [1], water [2] or gas [3] and microfiltration by membranes, but also to process fuel cell electrodes [4], for thermal energy storage devices [5], and for sound [6] or thermal insulation [7]. All these applications are typically developed with isotropic porous materials.…”
Section: Introductionmentioning
confidence: 99%